Improving Junior High School Students' Mathematics Learning Outcomes Using the Make A Match Type Cooperative Learning Model - Anjelina Yemerice Tae (Program Studi Pendidikan Matematika, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
This study aims to investigate the improvement of mathematics learning outcomes of junior high school students using the cooperative learning model of make a match. This research is a classroom action research. The subjects of this study were 21 students of class VIII B of SMP Satap Negeri Nakol. The results of the study show that based on the analysis of data in cycle I, out of 21 students who took the test, 12 students achieved completeness, while 9 other students were not complete, so the classical completeness of students in cycle I was 57.14% and in cycle II the student's learning outcomes increased to 80.95% with 17 students completing and 4 students not completing. The results of the study conducted in two cycles show that the use of the cooperative learning model of make a match is able to improve student learning outcomes.